The Effect of Fennel Extract Solution on Surface Roughness and Light Absorption of Flexible Denture Base Material - Khalaf, Hanan A bdulrahman; Israa Mohammed Hummudi (American Journal of Biomedicine and Pharmacy, 2026)
Background: commercially used chemical dental cleansers adversely affect mechanical properties of denture, therefore there is need for finding alternative which will not change the surface properties of denture base material. Aim: the aim of this work is to evaluate the effect of fennel’s extract solution on Surface roughness and light absorption of flexible denture base material. Materials and method: 40 specimens were prepared from thermoplastic acrylic resin with dimension of (65×10×2.5mm) and divided into control and experimental groups(n=20) according to the immersion time which done at 15 days and 30 days. Surface roughness test was performed for control group by digital surface roughness tester. Light absorption test was done by visible spectrophotometer. Results: The highest average value for surface roughness was found in the control group, while the lowest average value of surface roughness was found in the experimental group, but statistically no significant difference. For Visible light absorption, there was significant difference between experimental and control group at day 15 and 30. Conclusion: Based on our findings, the fennel extract did not adversely affect the surface roughness and light absorption of flexible denture base surface.